10 movies and documentaries with an "inclusion message" - Luu, Trang Delos (Institutional Knowledge at Singapore Management University, 2018)
Social inclusion ideally involves a multi-targeted approach that addresses a medley of contextual factors including cultural customs and access to resources to ascertain a degree of assimilation. Fostering collaboration between different social identities has the power to catalyse social mobility for marginalised communities through increased participation and access to societal opportunities generally barred by conventional norms. To this end, fi lms have the special ability to draw focus to specifi c circumstances by capturing the engaging stories and experiences of unique characters to offer multitudes of perspective. The following 10 fi lms highlight stories of and by trailblazing outsiders who endeavour to expose and overcome the challenging barriers of unfamiliar yet desired social worlds, and pave the way for greater social inclusion.